Efficacy and safety of nebulized inhalation vs. intramuscular delivery of interferon α1b injection for paediatric patients with viral respiratory diseases: a systematic review and meta-analysis - Yang, Lixing; Cao, Lu; Zhu, Yaning; Zhao, Ying; Zhang, Peng (Frontiers in Pediatrics, 2025)
ObjectivesTo systematically evaluate the efficacy and safety of nebulized inhalation vs. intramuscular delivery of interferon α1b (IFN α1b) for paediatric patients with viral respiratory diseases.MethodsA comprehensive search of databases including PubMed, Web of Science, Cochrane, Embase, China National Knowledge Infrastructure (CNKI), and China Biology Medicine disc (Sinomed) was conducted to identify relevant literature on the use of interferon α1b in children. The search timeframe spanned from database inception to April 2025.ResultsA total of 16 studies involving 2002 patients were included. The meta-analysis revealed that the overall efficacy rate in the nebulized inhalation group (94.85%) was significantly greater than that in the intramuscular injection group (82.39%) (P < 0.00001). Consistent results were observed in the herpangina and bronchiolitis subgroup analyses (P < 0.0001). With respect to drug safety, the meta-analysis results revealed that the incidence rate of adverse reactions in the nebulized inhalation group (1.58%) was significantly lower than that in the intramuscular injection group (4.60%) (P = 0.003). The studies had no significant publication bias, and sensitivity analysis suggested that the results were reliable.ConclusionCompared with intramuscular injection, nebulized inhalation significantly increased the efficacy and safety of IFN α1b in treating paediatric patients with viral respiratory diseases. For children with both herpangina and bronchiolitis, nebulized inhalation was more effective; however, no significant difference was found in the incidence of adverse reactions. In the future, multicentre, large-scale randomized controlled trials should be conducted to further validate these conclusions.